2021
DOI: 10.1109/access.2021.3102020
|View full text |Cite
|
Sign up to set email alerts
|

Research on the Processing of Coal Mine Water Source Data by Optimizing BP Neural Network Algorithm With Sparrow Search Algorithm

Abstract: Coal mine safety is crucial to the healthy and sustainable development of the coal industry, and coal mine flood is a major hidden danger of coal mine accidents. Therefore, the processing of coal mine water source data is of great significance to prevent mine water inrush accidents. In this experiment, the laser induced fluorescence technology was used to obtain the data information of 7 water sources with the assistance of laser. The laser emission power was set to 100 mw, and the 405 nm laser was emitted to … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
14
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 59 publications
(25 citation statements)
references
References 21 publications
0
14
0
Order By: Relevance
“…Due to the high sensitivity of BPNN to weight and threshold values [41]. In the continuous iteration, if the return error is large, the autonomous learning time consuming will be greatly increased.…”
Section: B Improved Temperature Inversion Model Constructionmentioning
confidence: 99%
“…Due to the high sensitivity of BPNN to weight and threshold values [41]. In the continuous iteration, if the return error is large, the autonomous learning time consuming will be greatly increased.…”
Section: B Improved Temperature Inversion Model Constructionmentioning
confidence: 99%
“…However, hydrochemical methods require sampling experiments to determine the various concentrations of ions and molecules in the solution and eliminate any interference that could affect the rapid identification of water sources [33]. At the same time, many water inrush disasters have shown that the water inrush mode and the inrush points may involve various water sources [34].…”
Section: Introductionmentioning
confidence: 99%
“…Traditional methods of water temperature and water level discrimination or direct analysis the hydrochemical data are being replaced by semi-quantitative analysis methods. Most widely used methods are combined with mathematical theory analysis, such as the cluster analysis method (Panagopoulos et al 2016;Zhang et al 2019), fuzzy mathematics method (Tiantian et al 2019), grey theory method (Ju et al 2019), bayesian discriminant method (Bogardi et al 1982;Wu et al 2016), fisher feature extraction algorithm (Wang et al 2021), GIS theoretical method (Donglin et al 2012), SVM algorithm (Ma et al 2018), and neural network algorithm (Chen et al 2021;Yan et al 2021). The above identification models are generally fast and effective, and machine learning methods have better applicability and advantages in identifying water inrush sources.…”
Section: Introductionmentioning
confidence: 99%